Transformasi Akuntansi Digital: Implikasi Artificial Intelligence, Big Data, Blockchain, Dan Xbrl TeRhadap Kerangka Konseptual Pelaporan Keuangan - Jonathan Marchelino; Oktaf Ndruru; Hamonangan Siallagan (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has significantly transformed accounting and financial reporting practices. Technologies such as Artificial Intelligence (AI), Big Data, Blockchain, and eXtensible Business Reporting Language (XBRL) encourage faster, more accurate, transparent, and relevant collection, processing, analysis, and presentation of financial information. This study aims to analyze the implications of the application of digital technology on the conceptual framework of financial reporting. The method used is a literature study by reviewing scientific journals, books, accounting standards, and related publications. The results of the study indicate that AI increases data processing efficiency and predictive capabilities, Big Data expands information sources that support reporting relevance, Blockchain increases transparency and reliability through decentralized recording, while XBRL facilitates the exchange and standardization of financial data. The integration of these technologies presents opportunities and challenges in maintaining relevance, accurate representation, comparability, timeliness, and verifiability of information, so the accounting profession and regulators need to continue to adapt in the digital era.